Respiratory support for patients with COVID‐19: A national survey of respiratory departments in England. (2nd September 2022) - Bartlett‐Pestell, Sam; Navaratnam, Annakan V.; Adelaja, Ini; Allen, Martin
Abstract: Objective: We developed a national survey to assess the changes implemented by respiratory departments across England in response to the first wave of the COVID‐19 pandemic. Methods: An online survey was sent to the respiratory clinical leads in 132 NHS trusts in England. The survey was open between 10 August 2020 and 25 September 2020. Results: Fifty‐three responses (42%) are included in our results. The total number of non‐critical care led Level 2 beds (requiring care for single organ failure—capable of managing continuous positive airways pressure, CPAP) increased by 159% at peak COVID activity from levels prior to COVID‐19. CPAP was used solely in side‐rooms in 9% of sites, and 57% and 31% of sites used CPAP in closed bays and closed wards, respectively. Fifteen sites (28%) reported shortages of non‐vented non‐invasive ventilation (NIV) masks and 12 sites (23%) CPAP machines. There was regional variation. Conclusions: The number of beds capable of managing patients requiring CPAP increased significantly. We found deviations from previous standards of care, which likely reflects the pressure faced by hospitals in managing patients with COVID‐19. The regional variation in equipment shortages suggests moving resources between regions may have been beneficial. Abstract : We developed a national survey to assess the changes implemented by respiratory departments across England in response to the first wave of the COVID‐19 pandemic. The number of beds capable of managing patients requiring CPAP increased significantly. We found deviations from previous standards of care which likely reflects the pressure faced by hospitals in managing patients with COVID‐19.